Coffee and non‐alcoholic fatty liver disease: Brewing evidence for hepatoprotection?. Issue 3 (March 2014) - Chen, Shaohua; Teoh, Narci C; Chitturi, Shiv; Farrell, Geoffrey C
Abstract Coffee is one of the most popular beverages in the world. Several studies consistently show that coffee drinkers with chronic liver disease have a reduced risk of cirrhosis and a lower incidence of hepatocellular carcinoma regardless of primary etiology. With the increasing prevalence of non‐alcoholic fatty liver disease (NAFLD) worldwide, there is renewed interest in the effect of coffee intake on NAFLD severity and positive clinical outcomes. This review gives an overview of growing epidemiological and clinical evidence which indicate that coffee consumption reduces severity of NAFLD. These studies vary in methodology, and potential confounding factors have not always been completely excluded. However, it does appear that coffee, and particular components other than caffeine, reduce NAFLD prevalence and inflammation of non‐alcoholic steatohepatitis. Several possible mechanisms underlying coffee's hepatoprotective effects in NAFLD include antioxidative, anti‐inflammatory, and antifibrotic effects, while a chemopreventive effect against hepatocarcinogenesis seems likely. The so‐far limited data supporting such effects will be discussed, and the need for further study is highlighted.